Immunization Initiation Among Infants in the Oregon Health Plan - Henderson, Jessica W. (© American Journal of Public Health 2006, 2006)
Infants who start receiving immunizations on time are more likely to be up to date at age 2 years. Among 39708 infants aged 3 months covered by the Oregon Health Plan (expanded Medicaid), those who did not have health care coverage within the first month of life were less likely to start receiving immunizations on time. Also at risk were infants in foster care, in subadoptive care, who were blind or disabled, who were Native American or Black, or whose mothers were not covered by the Oregon Health Plan.